A semiotic analysis of Ganep Tradisi Solo visual identity and packaging modernization strategy - Yuannita Steila; Yana Erlyana (Universitas Indraprasta PGRI, 2026)
The visual identity of traditional product packaging plays a significant role in maintaining brand relevance amid changing consumer preferences and intense market competition. This study analyzes the visual identity of the 90-gram Roti Kecik plastic pouch from Ganep Tradisi Solo as a basis for formulating a modernization strategy that remains rooted in cultural values. Using a descriptive qualitative approach, the research employs a structural semiotic framework (Roland Barthes’ denotation and connotation) integrated with social semiotics (Kress and van Leeuwen’s visual grammar) and heritage branding theory to explore the typography, color, illustration, and packaging structure elements. The analysis focuses on how these elements construct symbolic meaning, traditional narratives, and brand positioning in the contemporary market. The results demonstrate that while Ganep's visual elements effectively function as denotative markers of Surakarta's cultural heritage, the connotative delivery is visually fragmented and lacks the structural simplicity preferred by Generation Z. This study contributes to the field by establishing a